2004
DOI: 10.1562/0031-8655(2004)79<76:aocrtt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cellular Response to Thermal Laser Injury Through Bioluminescence Imaging of Heat Shock Protein 70¶†

Abstract: Assessment of laser-induced tissue damage is not complete without an investigation into the resulting cellular and molecular changes. In the past, tissue damage was quantified macroscopically by visual effects such as tissue mass removal, carbonization and melting. Microscopically, assessment of tissue damage has been typically limited to histological analysis of excised tissue samples. In this research, we used heat shock protein (hsp70) transcription to track cellular response to laser-induced injury. A stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 31 publications
4
58
0
Order By: Relevance
“…For example, cells exposed to 45°C for 15 min were observed to undergo transient G 2 block, while when exposed to 45°C for 30 min, they exhibited a long lasting G 2 phase and a late S-phase block [73]. The CSR mechanism is well documented in the literature [66][67][68][69][74][75][76][77], and the general consensus is that cells activate these mechanisms to combat and survive hyperthermic stress. CSR mechanisms involve many intracellular pathways, including redox, DNA sensing and repair, molecular chaperones, proteolysis, energy metabolism, and apoptosis [78].…”
Section: Thermal Effects On Mammalian Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cells exposed to 45°C for 15 min were observed to undergo transient G 2 block, while when exposed to 45°C for 30 min, they exhibited a long lasting G 2 phase and a late S-phase block [73]. The CSR mechanism is well documented in the literature [66][67][68][69][74][75][76][77], and the general consensus is that cells activate these mechanisms to combat and survive hyperthermic stress. CSR mechanisms involve many intracellular pathways, including redox, DNA sensing and repair, molecular chaperones, proteolysis, energy metabolism, and apoptosis [78].…”
Section: Thermal Effects On Mammalian Cellsmentioning
confidence: 99%
“…These proteins, collectively referred to as minimal stress proteins, are significantly upregulated by cells immediately after exposure to stress. The most widely studied family of minimal stress proteins are the heat shock proteins (Hsps), which includes Hsp70, Hsp40, Hsp60, and Hsp105 [66][67][68][69][74][75][76][77] (Fig. 4a, c).…”
Section: Thermal Effects On Mammalian Cellsmentioning
confidence: 99%
“…Among members of the Hsp family, Hsp70 (namely, HSP70.1 and Hsp70.2) is the most abundant as well as temperature sensitive (Beckham et al, 2004). It is an important "molecular chaperon" that can protect cells from heat damage as well prevent protein denaturation and apoptosis (Sonna et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Future efforts to confirm localized heating in cells during UVA photoactivation could be analyzed through heat shock protein expression, similar to studies with longer wavelengths of light. 47 Cell density has previously been shown to be significant in studying the mode of cell death for confluent cells and microcolonies. 31 By extrapolating this information, we confirmed that cell confluence also affected HeLa cell sensitivity to UVA light.…”
Section: Discussionmentioning
confidence: 99%